BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN AKDR - Juniarti, Rizky Auliah; Azizah, Zulfa Nur; Simamora, Janner Pelanjani; Hutabarat, Naomi Isabella (Ensiklopedia of Journal, 2025)
Abstract: According to data released by the Central Bureau of Statistics (BPS) in 2023, Indonesia's population has experienced a significant increase and reached around 275 million people. The impact of population problems if not handled properly will experience problems with the economy, environment, and politics. According to data obtained from the Sleman District Health Office in 2023, the average coverage of the use of Intrauterine Contraceptives (IUD) in the region reached 31.41%. The purpose of the study was to determine several factors associated with the use of IUDs. The research design used in this study was cross sectional. The research was conducted at the Mlati II Health Center in July 2023. The population was all active family planning users registered at the Mlati II Health Center. The sample amounted to 90 respondents. The sampling technique used in this study was Simple Random Sampling. Data analysis was carried out univariate and bivariate. The results showed a relationship between knowledge (p value: 0.00) and husband support (p value: 0.00) on the use of IUD. It is recommended for mothers and husbands to be able to actively seek information about the benefits and advantages of IUD contraception.Keywords: IUD, Husband Support, Knowledge